PROPOSAL OF THE COST MINIMIZATION PROCEDURE IN THE INVENTORY CONTROL - Slavomira Szentivanyi (European Scientific Journal, ESJ, 2014)
Contemporary material flow management is evaluated by criteria with impact on the cost savings at the local level of each department. From a global point of view of the whole enterprise there is formed an antagonistic relationship between departments. It is not possible to assess the impact of the results of one department on the results of the whole enterprise. The paper opens a new possibility in solution of business costs savings on a global scale.